The Complications of Jejunostomies in the Post-Operative Period - Banerjee, Tamalina (Trinity Student Medical Journal, 2003)
Objectives: To determine the type and frequency of complications relating to jejunostomy feeding tubes following oesophagectomy for oesophageal malignancy. Methods: A retrospective analysis of 25 patients who had undergone oesophagectomy. Physicians’ notes, nursing and nutrition notes were analysed and any complication relating to the jejunostomy tube was recorded. Results: Of the 25 patients reviewed, 14 (56%) had mild complications associated with the jejunostomy tube. Three (12%) experienced diarrhoea, 3 (12%) had abdominal distention, 3 (12%) bloating, 3 (12%) cramping, 1 (4%) constipation, 1 (4%) reflux. In 13 patients, all of the symptoms were mild and resolved in one to two days with treatment. One patient who developed diarrhoea died of sepsis before an outcome could be determined. Conclusion: The complications relating the jejunostomy feeding were minor, short-lived and easily treatable. These minor complications are acceptable considering the nutritional advantages that jejunostomy tubes offer patients post-operatively.